The all-consuming world - Khaw, Cassandra (Erewhon Books, 2021)
In Locus and British Fantasy Award nominee Cassandra Khaw's first novel, a crew of diminished former criminals get back together to solve the mystery of their last, disastrous mission. But the universe's highly-evolved AI has its own opposing agenda... and will do whatever it takes to keep humans from ever controlling them again.